A Porcine Sepsis Model With Numerical Scoring for Early Prediction of Severity - Rutai, Attila; Zsikai, Bettina; Tallósy, Szabolcs Péter; Érces, Dániel; Bizánc, Lajos; Juhász, László; Poles, Marietta Zita; Sóki, József; Baaity, Zain; Fejes, Roland; Varga, Gabriella; Földesi, Imre; et al. (Frontiers in Medicine, 2022)
Introduction: Sepsis can lead to organ dysfunctions with disturbed oxygen dynamics and life-threatening consequences. Since the results of organ-protective treatments cannot always be transferred from laboratory models into human therapies, increasing the translational potential of preclinical settings is an important goal. Our aim was to develop a standardized research protocol, where the progression of sepsis-related events can be characterized reproducibly in model experiments within clinically-relevant time frames. Methods: Peritonitis was induced in anesthetized minipigs injected intraperitoneally with autofeces inoculum (n=27) or with saline (sham operation; n=9). The microbial colony-forming units (CFUs) in the inoculum were retrospectively determined. After awakening, clinically relevant supportive therapies were conducted. Nineteen inoculated animals developed sepsis without a fulminant reaction. Sixteen hours later, these animals were re-anesthetized for invasive monitoring. Blood samples were taken to detect plasma TNF-α, IL-10, big endothelin (bET), high mobility group box protein1 (HMGB1) levels and blood gases, and sublingual microcirculatory measurements were conducted. Hemodynamic, respiratory, coagulation, liver and kidney dysfunctions were detected to characterize the septic status with a pig-specific Sequential Organ Failure Assessment (pSOFA) score and its simplified version (respiratory, cardiovascular and renal failure) between 16–24h of the experiments. Results: Despite the standardized sepsis induction, the animals could be clustered into two distinct levels of severity: a sepsis (n=10; median pSOFA score=2) and a septic shock (n=9; median pSOFA score=8) subgroup at 18 h of the experiments, when the decreased systemic vascular resistance, increased DO2 and VO2, and markedly increased ExO2 demonstrated a compensated hyperdynamic state. Septic animals showed severity-dependent scores for organ failure with reduced microcirculation despite the adequate oxygen dynamics. Sepsis severity characterized later with pSOFA scores was in correlation with the germ count in the induction inoculum (r=0.664) and CFUs in hemocultures (r=0.876). Early changes in plasma levels of TNF-α, bET and HMGB1 were all related to the late-onset organ dysfunctions characterized by pSOFA scores. Conclusions: This microbiologically-monitored, large animal model of intraabdominal sepsis is suitable for clinically-relevant investigations. The methodology combines the advantages of conscious and anesthetized studies, and mimics human sepsis and septic shock closely with the possibility of numerical quantification of host responses.